The Influence Of Motivation, Supervision, and Leadership On Employee Discipline At The Office Of The National and Political Unity Agency (KESBANGPOL) Seram Bagian Barat District - Semuel Souhoka (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to determine the effect of motivation, supervision, and leadership on the work discipline of employees of the Office of the National and Political Unity Agency (Kesbangpol) of West Seram Regency. The research approach that will be used in this research is a quantitative approach. In this study, the population in this study were all employees at the Office of the West Seram Regency National and Political Unity Agency (Kesbangpol) which amounted to 35 people, where the entire population was used as a research sample using the saturated sample method, the sample used was 35 people. The data were analyzed using the classical assumption test, multiple linear regression, hypothesis testing and the coefficient of determination test. The results of the study found that motivation, supervision, leadership partially and simultaneously affect the work discipline of employees of the Office of the National and Political Unity Agency (Kesbangpol) of West Seram Regency.